2015
DOI: 10.1128/jvi.00109-15
|View full text |Cite
|
Sign up to set email alerts
|

A Role for 3- O -Sulfated Heparan Sulfate in Promoting Human Cytomegalovirus Infection in Human Iris Cells

Abstract: H uman cytomegalovirus (HCMV), a member of the betaherpesvirus family, is the leading cause of congenital neurological complications in neonates as a result of maternal infection (1-4). Among immunocompromised patients-especially those with an organ transplant, chemotherapy, or AIDS-the reactivation of virus causes life-threatening diseases, such as gastroenteritis, encephalitis, pneumonitis, and graft rejection (5-7). In addition, HCMV infection is also implicated in widespread ocular damage and potential vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…Mutant mouse lung endothelial cell lines were from adult mice were mutated for specific sulfotransferase enzymes by a CRISPR-Cas9 based gene editing system 38 45 46 . Since previous studies showed that 3- O -S HS is important for HCMV entry in human iris stromal cells 28 , we analyzed virus replication in Hs3st1 and Hs3st4 (Glucosaminyl 3- O -sulfotransferase 1 and 4, respectively) knockout cell lines as well as the Hs3st1/4 double knockout cell line. At high (5.0) as well as low (0.01) multiplicity of infection (MOI), MCMV growth was significantly reduced in the single Hs3st1 and Hs3st4 knockouts as well as in the double Hs3st1/4 knockouts, indicating that 3- O -sulfation of HS is important for HCMV infection (Fig 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant mouse lung endothelial cell lines were from adult mice were mutated for specific sulfotransferase enzymes by a CRISPR-Cas9 based gene editing system 38 45 46 . Since previous studies showed that 3- O -S HS is important for HCMV entry in human iris stromal cells 28 , we analyzed virus replication in Hs3st1 and Hs3st4 (Glucosaminyl 3- O -sulfotransferase 1 and 4, respectively) knockout cell lines as well as the Hs3st1/4 double knockout cell line. At high (5.0) as well as low (0.01) multiplicity of infection (MOI), MCMV growth was significantly reduced in the single Hs3st1 and Hs3st4 knockouts as well as in the double Hs3st1/4 knockouts, indicating that 3- O -sulfation of HS is important for HCMV infection (Fig 9).…”
Section: Resultsmentioning
confidence: 99%
“…This susceptibility to O -desulfated heparins can be transferred to HSV-1 by recombinant transfer of the gene for glycoprotein C (gC-2) from HSV-2 27 . It was recently established that 3- O -S HS are important for HCMV entry in human iris stromal (HIS) cells 28 . The expression of Hs3st in HIS cells promoted HCMV internalization, while pretreatment of HIS cells with heparinase enzyme or treatment with anti-3- O -S HS (G2) peptide significantly reduced HCMV plaques/foci formation.…”
Section: Introductionmentioning
confidence: 99%
“…While p5R and p5R D reduce HCMV infection in all cell types, there are subtle differences in the percent reduction that potentially reflects differences in HS expression on the cell. It is known that CMV uses a 6-O-sulfated and 3-O-sulfated heparan sulfate for entry (Baldwin et al, 2015; Borst et al, 2013). Our data suggest that p5R D binds to a specific subset of HS, that is different from HS targeted by the previously characterized p5+14 and the HSV-1 entry inhibitor peptide, G2 (Dogra et al, 2015; Tiwari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CMVs utilize HSGPs for their initial attachment to the cell and subsequent initiation of infection (Compton et al, 1993). Previous studies have shown that HCMV may preferentially bind to 6-O-sulfated or 3-O-sulfated heparan sulfate moieties during viral entry (Baldwin et al, 2015; Borst et al, 2013). The distribution of HS on host cells in addition to viral preference for specific subtypes of HS, make this structure a potential anti-CMV therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Fondaparinux is a common oligosaccharide used in biophysical studies of GAG interactions with proteins, in which a readily available GAG oligosaccharide of the defined structure is required for the study [17,[18][19][20]. The synthetic pentasaccharide includes a 3-O-sulfated glucosamine, which has been implicated previously in adhesion of some viruses to cell surfaces [21,22]. The experimental characterization and computational modeling of the contact sites between gp120 and fondaparinux will provide a better understanding of how gp120 interacts with fondaparinux and suggest possible methods for blocking the entry of the HIV virus into the host cells.…”
Section: Introductionmentioning
confidence: 99%